2003
DOI: 10.1038/sj.gt.3301904
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular trafficking and enhanced in vivo antitumour activity of a non-virally delivered P27-VP22 fusion protein

Abstract: VP22, a structural protein from herpes simplex virus type I, exhibits the unique property of intercellular trafficking. This protein is exported from primary expressing cells and subsequently imported into neighbouring cells. This property is conserved when VP22 is genetically fused to a protein, making it a promising tool to enhance the delivery of a gene product. We chose to study the intercellular transport and biological effect of a fusion protein between the putative tumour suppressor gene p27 Kip1 and VP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…Moreover, the absence of b-galactosidase expression with Flp alone could be accountable to the Flp thermolability at 371C. 55 An increase in protein stability mediated by VP22 could explain these results as well as studies with shortlived proteins such as p53 and p27 Kip140,41,43 and, indeed, we have found that VP22 could dramatically increase the stability of d1EGFP, a GFP version with a very short halflife (data not shown).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Moreover, the absence of b-galactosidase expression with Flp alone could be accountable to the Flp thermolability at 371C. 55 An increase in protein stability mediated by VP22 could explain these results as well as studies with shortlived proteins such as p53 and p27 Kip140,41,43 and, indeed, we have found that VP22 could dramatically increase the stability of d1EGFP, a GFP version with a very short halflife (data not shown).…”
Section: Discussionmentioning
confidence: 65%
“…39 This property of VP22 was first demonstrated with the protein alone or fused to GFP, and it was then extended to other fusion partners that have a therapeutic potential in gene therapy. 37,38,[40][41][42][43] Using this very attractive strategy, an increase in the BE was reported with TK/ VP22 versus TK alone; however, the cytotoxic effect enhancement was very limited, 37,38 and it was only detected when a high percentage of cells expressed the fusion protein. 37 Based on these results, we hypothesized that TK30 fused to VP22 should increase the BE independently of the level of connexins.…”
Section: Introductionmentioning
confidence: 99%
“…However, the transfection efficiency is still low (o1% of the tumor cells), but we previously demonstrated that it is sufficient to successfully deliver p53-, bax-or p27-encoding plasmids. [26][27][28] In this study, we show that despite this very low transfection efficiency, a significant reduction of tumor growth can be observed after direct intratumoral injection of HERV-W-or GALV-, but not RD-FMG-encoding plasmids. This strong antitumor response suggests that FMG genes and especially HERV-W and GALV are very potent and promising tools for the treatment of human lung tumors, especially in immunecompetent animals where we know that this direct cell-killing activity of FMG will also be supported by release of highly immunogenic exosome-like vesicles.…”
Section: Fmg-mediated Tumor Therapy E-h Lin Et Almentioning
confidence: 65%
“…29 Fusion proteins between VP22 and a therapeutic polypeptide were thus successfully used for in vivo tumor therapy although conflicting results have also been reported. 27,28,[30][31][32][33][34][35] Positive gene therapy results using suicide genes like the herpes simplex type-1 thymidine …”
Section: Discussionmentioning
confidence: 99%
“…17 Conversely, several reports showed efficient transport in living cells, 3,19 regardless of the fixation method. 20 In our experiments, VP22-GFP spreading to the nuclei of acceptor cells was detected by fluorescence microscopy both in fixed and unfixed cells (Figure 2a, b, e and f); however, FACS analysis revealed an increase in the number of GFP-positive cells only after fixation with either 3% formaldehyde, 100% methanol or both (data not shown). This could be due to the fact that the level of protein in the recipient cells was below the level of detection in living cells, while fixation may have resulted in intracellular protein concentration.…”
Section: Vp22-mediated Trafficking Under Hypoxia O Greco Et Almentioning
confidence: 46%